PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN (PT. Asuransi Jasa Indonesia (Persero) Kantor Pusat) - Muhammad Halilintar; Imelda Taurina Ghagho (Jurnal Manajemen FE-UB, 2018)
This study aims to determine the extent of the influence of organizational culture, leadership, on employee performance through job satisfaction at PT. Asuransi Jasa Indonesia (Persero) Head Office.The data used in this study are primary data collected from respondents' answers based on the questionnaire given, which is as much as 85 people. Data processing method using path analysis method with the help of SPSS Version 22.0. Statistical testing uses the significance test of individual parameters (t test) and simultaneous significance test (F test).The results of the study show that simultaneously organizational culture, leadership, job satisfaction have a significant effect on employee performance. Partially, it shows that analysis 1: Organizational culture variables have a significant effect on employee performance, while analysis 2: leadership variables have a significant effect on employee performance and in analysis 3: Variable employment variables have a significant effect on employee performance. Keywords: Organizational Culture, Leadership, Job Satisfaction and Employee Performance.